Conjunturas da saúde do usuário-trabalhador e perspectivas na atenção básica - Trindade, Maiara Leal da (2024)
Illnesses and health problems for user-workers represent a challenge for health teams, especially in Primary Care. Therefore, it is necessary to understand health care for user-workers based on the practice of nurses and municipal officials responsible for implementing the National Workers' Health Policy in this scenario. Objective: to analyze health care for user-workers provided by nurses and those responsible for the implementation of the National Workers' Health Policy, in the context of Primary Care, in the central region of Rio Grande do Sul. Method: research approach qualitative, with an exploratory-descriptive character. It took place from April to August 2023, in Primary Care health services in municipalities under the responsibility of the Occupational Health Reference Center in the central region of Rio Grande do Sul, with Primary Care nurses and municipal managers responsible for implementing the National Health Policy. Workers' Health. The “snowball” technique was used to select the sample, the focused interview was used as a data collection technique and Critical Discourse Analysis guided the analysis of the findings. The study followed the ethical principles of research with human beings. Results: nurses realize that health care for user-workers is not valued in Primary Care and the care provided is focused on reporting illnesses and work-related injuries. Municipal officials reported a lack of knowledge about their responsibilities in relation to the health of user-workers; feeling of submission of their practice to municipal political interests; work overload and do not indicate facilities for developing their work. Final considerations: in health care for user-workers, Primary Care professionals face challenges such as: lack of institutional support, work overload, influence of political interests and unpreparedness of the multidisciplinary team.